2010
DOI: 10.1108/02637471011051282
|View full text |Cite
|
Sign up to set email alerts
|

Workplace impact of social networking

Abstract: Purpose -This paper aims to examine the impact of social networking in the workplace and to assess its use as an effective business tool. Design/methodology/approach -The paper examines positive and negative perceptions of social networking in the workplace and provides a critical review of literature in the area. The drivers of, and barriers to, change are explored, and whether the reasons for some organisations prohibiting or restricting social networking in the workplace are well-founded or corporate suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 26 publications
2
98
0
1
Order By: Relevance
“…Leidner et al (2010) found that new employees performed better and faster after using the ESM when building new relationships and facilitating quick tacit and explicit knowledge transfer. Collective knowledge was improved when using ESM hence contributing to the job performance of the employees (Bennett et al 2010). Therefore this study hypothesizes the following:…”
Section: Performancementioning
confidence: 95%
“…Leidner et al (2010) found that new employees performed better and faster after using the ESM when building new relationships and facilitating quick tacit and explicit knowledge transfer. Collective knowledge was improved when using ESM hence contributing to the job performance of the employees (Bennett et al 2010). Therefore this study hypothesizes the following:…”
Section: Performancementioning
confidence: 95%
“…Leidner et al (2010) found out that the ability of employees to access Facebook at work was a great incentive for new hire retention as they can be socially connected with family, friends, and other coworkers in the workplace. Social networking site use in the workplace can be an important means of communication among the company's internal and external stakeholders which aids knowledge dissemination and communication (Bennett et al, 2010;Leader-Chivée & Cowan, 2008). The means of communication social networking sites can provide users with, but are not limited to, email, file sharing, blogging, instant messaging, and chatting.…”
Section: Cultivating Modest Human Resource Practices Through Social Nmentioning
confidence: 99%
“…This positive attitude has reverberated in the findings of the literature review that social media timeouts started as mental appetite disinfectants, it revives the mind to be able to undertake on unfinished assignments with a greater level of attentiveness. In fact, enough access to SMPs can progress employee productivity (Bennett et al, 2010). The decision to statement C1 meant that respondents understood the significance of SMPs regarding minute break.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%